PENDIDIKAN KARAKTER BANGSA DALAM PUISI “MALU (AKU) JADI ORANG INDONESIA” KARYA TAUFIQ ISMAIL - Aning Ayu Kusumawati (Adabiyyāt: Jurnal Bahasa dan Sastra, 2013)
Object of discussion in this study is the Taufik Ismail's poem, which entitled “Malu (Aku) Jadi Orang Indonesia” (MAJOI). Core issues to be addressed in this study can be formulated as follows: the themes related to the value of the nation's main character education at work MAJOI Taufiq's poems and the work of key themes of character education in the nation's poetry Taufiq Ismail MAJOI. To answer the above formula researchers uses thematic studies. In reviewing the themes in the poetry MAJOI the researcher refers to the values of the nation's character issued by the Guidelines for Character Education, Ministry of National Education of Jakarta in 2011. This research finds fourteen social themes and two key themes, namely the collapse of morals and a sense of nationalism as well as patriotism.